Inside a Shari'ah court - Hamid, Ruhi ([Australia] : BBC, 2008)
Spotlighting an outspoken judge determined to convey the benefits of Islamic law, the film presents cases, verdicts, and sentences that clearly illustrate ways in which Shari'ah is implemented in Nigeria.
Title from title screen
executive producer, Roger Graef ; executive producer BBC, Louise Norman
Host and narrator, Ruhi Hamid
dvd format
Keywords: Islamic law -- Nigeria; Islamic courts -- Nigeria; Women's rights -- Nigeria